Advanced airway management during adult cardiac arrest: A systematic review. (June 2019) - Granfeldt, Asger; Avis, Suzanne R.; Nicholson, Tonia C.; Holmberg, Mathias J.; Moskowitz, Ari; Coker, Amin; Berg, Katherine M.; Parr, Michael J.; Donnino, Michael W.; Soar, Jasmeet; Nation, Kevin; Andersen, Lars W.; et al.
Abstract: Aim: To systematically review the literature on advanced airway management during adult cardiac arrest in order to inform the International Liaison Committee of Resuscitation (ILCOR) consensus on science and treatment recommendations. Methods: The review was performed according to PRISMA guidelines and registered on PROSPERO (CRD42018115556). We searched Medline, Embase, and Evidence-Based Medicine Reviews for controlled trials and observational studies published before October 30, 2018. The population included adult patients with cardiac arrest. Two investigators reviewed studies for relevance, extracted data, and assessed the risk of bias of individual studies. Results: We included 78 observational studies and 11 controlled trials. Most of the observational studies and all of the controlled trials only included patients with out-of-hospital cardiac arrest. The risk of bias for individual observational studies was overall assessed as critical or serious, with confounding and selection bias being the primary sources of bias. Three of the controlled trials, all published in 2018, were powered for clinical outcomes with two comparing a supraglottic airway to tracheal intubation and one comparing bag-mask ventilation to tracheal intubation. All three trials had some concerns regarding risk of bias primarily due to lack of blinding and variable adherence to the protocol. Clinical and methodological heterogeneity across studies, for both the observational studies and the controlled trials, precluded any meaningful meta-analyses. Conclusions: We identified a large number of studies related to advanced airway management in adult cardiac arrest. Three recently published, large randomized trials in out-of-hospital cardiac arrest will help to inform future guidelines. Trials of advanced airway management during in-hospital cardiac arrest are lacking.